Ephemeral venues: Architectural illustrations and depictions of the masses in Perón's 'New Argentina'. (1st March 2020) - Patruno, Luigi
During the Peronist years (1943–55), architect Jorge Sabaté designed several exhibitions and ephemeral installations to be erected in the central streets of Buenos Aires. These interventions were aimed at transforming the face of the city, repurposing its spaces for unprecedented uses and expressing the right 'the people' had gained to free time, outings and leisure. In this article, I examine the architectural illustrations that Sabaté appended to the rest of his plans. The incorporation into his drawings of the social practices of metropolitan strolling is one of the ways in which the Peronist exhibitions designed by Sabaté relate to urban culture. By staging the masses in these materials, Sabaté proposes a whole new form of conviviality in public space and depicts the popular sectors aspiring to a new lifestyle made possible by the intersection of technological progress and expanded access to consumer goods.